Discovery of a Novel β-xylosidase with Xylanase Activity and Its Application in the Production of Xylitol from Corncob Xylan - Meng Liang; Yu Lin; Lixin Sun; Hao Pang; Hang Wei; Ribo Huang; Yutuo Wei; Liqin Du (Fermentation, 2023)
Although β-xylosidases with xylanase activity are preferential for the hydrolysis of xylan and production of xylitol, reports on their use are scarce. In this study, a multifunctional β-xylosidase (XYL4) was identified. In addition to β-xylosidase activity, XYL4 also exhibited xylanase and low α-arabinosidase activity. The enzyme was able to hydrolyze bagasse xylan, oat spelt xylan, birchwood xylan, beechwood xylan, and corncob xylan, and showed the highest hydrolysis activity for corncob xylan. Structural modeling analysis indicated that XYL4 had an additional PA14 domain, which may play a key role in binding xylan substrates. Moreover, XYL4 was used to hydrolyze corncob xylan to produce xylose. When enzymatic hydrolysis and whole-cell catalysis were used to hydrolyze 100 g/L of corncob xylan, the xylose yields were 60.26% and 35.85%, respectively. Then, the Candida tropicalis was inoculated with the above hydrolysates for fermentation to produce xylitol. Using enzymatic hydrolysis and whole-cell catalysis, xylitol yields of 77.56% and 73.67% were obtained by C. tropicalis after the optimization of fermentation, respectively.